DEVELOPMENT TEACHING MATERIALS OF MATHEMATICS BASIC CONCEPTS BASED ON INTERNALIZATION OF ISLAMIC VALUE TO INCREASING CONCEPT UNDERSTANDING ABILITY - Mohamad Hariyono; Nuhyal Ulia (Tunas Nusantara, 2020)
Understanding the correct concepts can avoid misconceptions in basic mathematical material. There is still a mathematical misconception among PGSD students due to the low understanding of the concept. Lecturing the basic mathematical concepts as a subject that must be taken by PGSD students can be done by internalizing Islamic values in it. The concepts in mathematics are full of the values they contain including Islamic values. Therefore, it is necessary to have teaching materials on the basic concepts of mathematics based on the internalization of Islamic values. This study aims at 1) to determine the characteristics of teaching materials on the basic concepts of mathematics based on the internalization of Islamic values, 2) to improve understanding of mathematical concepts through learning with teaching materials on the basic concepts of mathematics based on the internalization of Islamic values. This research is a development research. Analysis of the data used included the validity analysis of teaching materials, analysis of practicality of teaching materials, analysis of the effectiveness of teaching materials, descriptive statistics, and Gain normalization tests. Improving the understanding of student mathematical concepts can be seen in the average score of 61.54 pretest and the post-test average score of 85.41. From the normalized gain test calculation shows an increase of 0.62 in the medium category. From the results of the study it is expected that the teaching materials of the basic concepts of mathematics based on the internalization of Islamic values can be applied in learning through various learning innovations with student centered.Keywords: Teaching materials of mathematics basic concepts in Elementary, Internalization of Islamic values, concept understanding Ability.